Question
upstudy study bank question image url

\( x ^ { \frac { 4 } { 3 } } - \sqrt[ 3 ] { x ^ { 2 } } - 72 = 0 \)

Ask by Lyons Murray. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = 27 \) and \( x = -27 \).

Solution

To solve the equation: \[ x^{\frac{4}{3}} - \sqrt[3]{x^2} - 72 = 0 \] **Step 1: Substitute** Let’s make a substitution to simplify the equation. Let: \[ y = x^{\frac{1}{3}} \] Then: \[ x = y^3 \] Now, express the original equation in terms of \( y \): \[ (x^{\frac{4}{3}}) = (y^3)^{\frac{4}{3}} = y^4 \] \[ (\sqrt[3]{x^2}) = (y^3)^{\frac{2}{3}} = y^2 \] Substituting these into the equation: \[ y^4 - y^2 - 72 = 0 \] **Step 2: Solve the Quartic Equation** Let’s set \( t = y^2 \). The equation becomes: \[ t^2 - t - 72 = 0 \] Solve for \( t \) using the quadratic formula: \[ t = \frac{1 \pm \sqrt{1 + 288}}{2} = \frac{1 \pm \sqrt{289}}{2} = \frac{1 \pm 17}{2} \] This gives: \[ t = 9 \quad \text{or} \quad t = -8 \] Since \( t = y^2 \) and \( y^2 \) cannot be negative: \[ t = 9 \implies y^2 = 9 \implies y = \pm 3 \] **Step 3: Back-Substitute to Find \( x \)** Recall that: \[ y = x^{\frac{1}{3}} \implies x = y^3 \] Thus: 1. If \( y = 3 \): \[ x = 3^3 = 27 \] 2. If \( y = -3 \): \[ x = (-3)^3 = -27 \] **Step 4: Verify Solutions** Plugging back into the original equation: - For \( x = 27 \): \[ 27^{\frac{4}{3}} - \sqrt[3]{27^2} - 72 = 81 - 9 - 72 = 0 \] - For \( x = -27 \): \[ (-27)^{\frac{4}{3}} - \sqrt[3]{(-27)^2} - 72 = 81 - 9 - 72 = 0 \] Both solutions satisfy the original equation. **Final Answer:** The real solutions are \( x = 27 \) and \( x = -27 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( x^{\frac{4}{3}} - \sqrt[3]{x^2} - 72 = 0 \), let's first make a substitution to simplify the expression. Let \( y = \sqrt[3]{x} \). Then, we can rewrite the equation as: \( y^{4} - y^{2} - 72 = 0 \). This is a quadratic in terms of \( y^{2} \). Let \( z = y^{2} \), transforming the equation into: \( z^{2} - z - 72 = 0 \). Now, we apply the quadratic formula: \[ z = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{1 \pm \sqrt{1 + 4 \cdot 72}}{2} = \frac{1 \pm \sqrt{289}}{2} = \frac{1 \pm 17}{2}. \] This results in \( z = 9 \) or \( z = -8 \). Since \( z = y^{2} \), it must be non-negative, so we discard \( z = -8 \) and take \( z = 9 \). Now, we have: \[ y^{2} = 9 \implies y = 3 \text{ or } y = -3. \] Recalling our substitution \( y = \sqrt[3]{x} \): 1. \( \sqrt[3]{x} = 3 \implies x = 27 \). 2. \( \sqrt[3]{x} = -3 \implies x = -27 \). Thus, the solutions to the original equation are: \[ \boxed{27 \text{ and } -27}. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy